Modelo Baldrige en una empresa manufacturera y su modelación de ecuaciones estructurales con mínimos parciales cuadrados. Caso de estudio (Baldrige model in a manufacturing company with partial least squares structural equation modeling. Case study) - Garza Villegas, Juan Baldemar; Lerma Castillo, Cristobal; Terriquez Nava, Omar (Facultad de Contaduría Pública y Administración, 2014)
Abstract. This article presents the content validity, concordance, relevance and reliability test of Cronbach Alpha for Model Malcolm Baldrige. The objective of this model is to improve the competitiveness between companies and United States business. And although still reach only in this country, the model can be applied in Mexican organizations as a tool. A structural equation model (SEM) is presented with the main constructs Malcome Baldrige model: leadership, strategic planning, customer and market focus, measurement, analysis and knowledge management, workforce focus, Process Management and results. Especially with the objective to evaluate the statistical significance between the constructs: leadership, strategic planning, customer and market focus, measurement, analysis and knowledge management, workforce focus and process management with the construct results. Which cronbach alphas indices vary between 0.6336 and 0.9048.